2016
DOI: 10.1186/s12864-016-2850-8
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-mRNA regulatory networking fine-tunes the porcine muscle fiber type, muscular mitochondrial respiratory and metabolic enzyme activities

Abstract: BackgroundMicroRNAs (miRNAs) are small non-coding RNAs that play critical roles in diverse biological processes via regulation of gene expression including in skeletal muscles. In the current study, miRNA expression profile was investigated in longissimus muscle biopsies of malignant hyperthermia syndrome-negative Duroc and Pietrain pigs with distinct muscle metabolic properties in order to explore the regulatory role of miRNAs related to mitochondrial respiratory activity and metabolic enzyme activity in skel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 95 publications
1
14
0
Order By: Relevance
“…miR-34a is an obesity-associated miRNA that attenuates metabolic hormone function [ 39 , 40 ]. It is upregulated in the Doroc pig and Göttingen Minipig obesity model [ 41 , 42 ]. In other cases, miR-34a expression has been found to be increased in human patients with liver disease and in a rat liver fibrosis model [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…miR-34a is an obesity-associated miRNA that attenuates metabolic hormone function [ 39 , 40 ]. It is upregulated in the Doroc pig and Göttingen Minipig obesity model [ 41 , 42 ]. In other cases, miR-34a expression has been found to be increased in human patients with liver disease and in a rat liver fibrosis model [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, high-phosphorus diets enhance energy metabolism through the utilization of free fatty acids released via lipolysis of white adipose tissue [ 59 ]. Accordingly, our previous study showed that miR-34a and miR-708 are upregulated in Duroc pigs, which are more obese than Pietrain [ 42 ]. This information links miR-34a to IP and TCHO, providing evidence of a functional link between IP, energy metabolism, genetic regulation of miRNA 34a and GALP.…”
Section: Discussionmentioning
confidence: 99%
“…This gene has been shown to be highly associated with slowtwitch and fast-twitch oxidative fibers (Liu et al, 2016). ADAM metallopeptidase domain 12 (ADAM12), a candidate in SSC 14_146 Mb has been shown to have higher expression in slow-oxidative muscle fibers in cattle (Coles et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…MiRNAs also play important roles in bone metabolism, bone-related diseases, and bone cell development and function [13][14][15][16]. Previous studies demonstrated that mRNA-miRNA regulatory networks affect different phenotypes, including endometrial receptivity in cattle, divergent muscle properties such as muscle fiber type, metabolic enzyme activity, and ATP production both in vivo pigs and in vitro in cell culture [17][18][19]. In the context of PU, the miRNA(s) involved and the role of host miRNA-mRNA and microbiota interactions remain unclear.…”
Section: Introductionmentioning
confidence: 99%